2011
DOI: 10.4161/spmg.1.3.18092
|View full text |Cite
|
Sign up to set email alerts
|

Reptilian spermatogenesis

Abstract: Until recently, the histology and ultrastructural events of spermatogenesis in reptiles were relatively unknown. Most of the available morphological information focuses on specific stages of spermatogenesis, spermiogenesis, and/or of the mature spermatozoa. No study to date has provided complete ultrastructural information on the early events of spermatogenesis, proliferation and meiosis in class Reptilia. Furthermore, no comprehensive data set exists that describes the ultrastructure of the entire ontogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…Reptiles, occupying a strategic position among terrestrial vertebrates, possess tubular testes in which multiple generations of germ cells develop within the seminiferous epithelia (Gribbins, 2011). It is well-known that many mammals have an associated reproductive pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Reptiles, occupying a strategic position among terrestrial vertebrates, possess tubular testes in which multiple generations of germ cells develop within the seminiferous epithelia (Gribbins, 2011). It is well-known that many mammals have an associated reproductive pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Additional spermiogenic data within multiple species of lizards could lead to increases in morphological data sets as well as more insightful hypotheses concerning reproductive biology in squamates. Only a handful of studies exist that give complete ultrastructural descriptions of spermiogenesis within the Squamata 9 . These studies have shown both conserved characteristics (i.e., nuclear elongation, acrosome development via Golgi vesicles) as well as unique characters (i.e., rough endoplasmic reticulum involvement in acrosome formation; 10 the absence of manchette microtubules) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…7,99,100 The usual pattern in birds is that the proximal and distal centrioles lie perpendicular to each other, in both the spermatid 23,31,42,48,49 and mature spermatozoon, 27,48,64,101 but those of Guinea fowl initially lie at right angle to each other, and this angle between them gradually becomes obtuse as the centriolar complex inserts in a deep vault in the nucleus of the spermatid. 58 Subsequently, the centrioles in the Guinea fowl are nearly in line-aligned, and the lumen of the proximal centriole often has some amorphous moderately electron-dense material in its anterior portion. The walls of both centrioles are thick, and a similar fuzzy amorphous material runs transversely between the proximal and distal centrioles (Fig.…”
Section: E959392-4 Volume 4 Issue 3 Spermatogenesismentioning
confidence: 99%
“…8D), and has been described in reptiles. 58 In mammals, the chromatoid body migrates caudally, disperses in the process, and ultimately disappears, 107 but its fate in the avian spermatid is not known. Its role in spermiogenesis is also not clearly understood.…”
Section: E959392-4 Volume 4 Issue 3 Spermatogenesismentioning
confidence: 99%